Afatinib in combination with GEMOX chemotherapy as the adjuvant treatment in patients with ErbB pathway mutated, resectable gallbladder cancer: study protocol for a ctDNA-based, multicentre, open-label, randomised, controlled, phase II trial. Issue 2 (28th February 2023) - Yang, Mao; Zhao, Yuhao; Li, Yongsheng; Cui, Xuya; Liu, Fatao; Wu, Wenguang; Wang, Xu-An; Li, Maolan; Liu, Yun; Liu, Yingbin
Abstract : Introduction: Gallbladder cancer (GBC) is an aggressive type of digestive system cancer with a dismal outcome. Given the lack of effective treatment options, the disease rapidly reoccurs and 5-year survival rate is <5%. Our team previously found that a significant percentage of GBC tissues harboured mutations of the ErbB-related pathway. Afatinib is a chemically synthesised drug specifically targeting the ErbB pathway mutations. However, its efficacy in the treatment of patients with GBC remains unknown. Circulating tumour DNA (ctDNA) refers to a proportion of cell-free DNA in the blood which is released by apoptotic and necrotic cells from tumours in situ, metastatic foci or circulating tumour cells. ctDNA-based liquid biopsy is a non-invasive pathological detection method that offers additional value to evaluate the therapeutic efficacy of antitumour drugs. Methods and analysis: We conduct a multicentre and randomised study on afatinib combined with gemcitabine and oxaliplatin (GEMOX) in patients with ErbB pathway mutated GBC. Clinical and biological evaluation involving ErbB pathway ctDNA detection will be made during the 3-year follow-up after participation. The primary objective of this clinical trial is to evaluate the clinical efficacy of afatinib. Disease-free survival is the primary end point and will be correlated with plasma ctDNA of patients in the treatment with afatinib. In addition, we will evaluate the sensitivity and specificity of plasma ctDNA for monitoring tumour recurrence and progression. Finally, we will assess the safety of afatinib by keeping an eye on the safety indicators. Ethics and dissemination: The study was approved by the medical-ethical review committee of Xinhua Hospital Affiliated to Shanghai Jiao Tong University School of Medicine and Renji Hospital Affiliated to Shanghai Jiao Tong University School of Medicine. The clinical trials results, even inconclusive, will be published in peer-reviewed journals. Trial registration number: NCT04183712 .